Fluvoxamine Provide a Gastro-Protection Against Vitiated Insult - Sada W. Abdulqader; Ibrahim M. Faisal; M. G. Saeed; Marwan M. Merkhan (Indian Journal of Forensic Medicine & Toxicology, 2022)
The etiology of peptic ulcer disease is multifactorial and remains an enigma over the last decades. The central parameter is the acid secretion; whose control is under the coordination of gastrin, acetylcholine, histamine, and prostaglandin. The treatment of peptic ulcers is a bi-armed tool, directed toward fighting microbial growth alongside acid suppression. However recent studies reported failure of the therapy due to recurrence of symptoms. Therefore, additional parameters should be considered including patient mood and psychological status. The present study aimed to introduce a new approach to the therapeutic regimen of ulcer disease using commonly used antidepressant drugs (fluvoxamine and fluoxetine) in a laboratory animal model of peptic ulcer induced by stress insult to act as a mood upset model in an attempt to mimic mood changes in human. The study was conducted on 4 groups of laboratory animals using control negative and control positive (misoprostol) against the tested drugs group (fluvoxamine and fluoxetine group). The result confirmed that fluvoxamine confers gastroprotective effects against ulcer insult compared to both fluoxetine or misoprostol groups. These results might significantly mean that antidepressant drugs could be utilized in peptic ulcer diseases or added at low doses to prevent ulcer insults due to whatever precipitating factors, such as, infection, alcohol, smoking, NSAIDs, and stress ulcer.